Development of Geography Teaching Material Supplements on Land Water Materials Based on Longalo Natural Tourism - Pratama, M. Iqbal Liayong; Nurfaika; Puspita Rahmat (Universitas Bengkulu, 2024)
This research aims to develop supplementary geography teaching materials based on Longalo natural tourism to increase understanding of inland water material among high school students. The ADDIE development model is used in developing this teaching material, which involves the stages of analysis, design, development, implementation, and evaluation. The research results show that the developed supplement book received a decent assessment from geography experts and teachers. The integration of Longalo natural tourism in learning materials enriches students' learning experiences and activates local potential as a valuable learning resource, per the concept of locally based education. These findings are essential to developing relevant geography teaching materials oriented toward using local resources to support environmental sustainability